PROXIMITY MANAGEMENT IN CRISIS CONDITIONS - Ion Dorin BUMBENECI; Corina Ana BORCOŞI; Dumitru CONSTANTINESCU (Management & Marketing)
The purpose of this study is to evaluate the level of assimilation for the terms "Proximity Management" and "Proximity Manager", both in the specialized literature and in practice. The study has two parts: the theoretical research of the two terms, and an evaluation of the use of Proximity management in 32 companies in Gorj, Romania. The object of the evaluation resides in 27 companies with less than 50 employees and 5 companies with more than 50 employees.